Harmônicas em geração distribuída - Santos, Silvério Penin y (2011)
This thesis identifies ways of mitigating the temporal harmonics caused by Non-Linear Loads (NLL) constituted by electronically switched loads which increase constantly, at the present time constituting 65% of the total in countries such as Brazil. The research involved identifies the solution for Distributed Generation (DG), that is to say, in plants fed by their own electrical generators working disconnected from the main, as occurs in situations of maintenance or emergency which lead to the interruption of the main. The solution presented in this study proposes that Synchronous Generators (SGs) of low sub transient reactances should be used as the solution. The research was undertaken by means of the development of the mathematical models used in the simulations by means of which the relationship between the reactances and the wave deformity of the voltage with Non Linear Loads became evident. Laboratory experiments validated the simulations. The spatial harmonics which are focused on only tangentially are disregarded seeing that the Synchronous Generators are produced with excellent wave forms with distortions of only 1% to 3%. The frequent quotation of norms or standards, especially of the IEC, the IEEE and the ABNT is meant to serve as a frame of reference for the thesis as regards the standards used by engineering firms in the projection and implantation of Electrical Generating Plants in Distributed Generation